Ecological combustion: the atmospherics of the bushfire as choreography - Rachel Fensham (Ambiances)
This paper examines the atmospheres generated by the elemental power of bushfires as embodiment, invention and reconstruction through choreography. Drawing upon Bachelard’s analysis of the phenomenology of fire leads to an appreciation of its substance and symbolic volatility, that is interlaced with an understanding of fire’s place in the Australian environment from both settler and indigenous perspectives. The close examination of several dances, that use different expressive vocabularies and structures, provides a means to access the experience of fire as an affect and a moving vital force in expressive formations that record real historical events and their impact. The atmosphere becomes then both the generator and the residue of movement. In conclusion, the paper gives attention to debates about climate change, in the context of the Anthropocene and ecofeminism, and suggests that the bushfire is more destructive than it ever has been, not because of its “wild nature” but because of the influence of humans in causing greater destruction. Greater awareness of the nature-culture of fire in performance is therefore valuable to other disciplines in so far as it facilitates what I’m calling “combustion” without loss of life, in recognition also of the experience of loss and regeneration.